Patterns of Mitochondrial TSPO Binding in Cerebral Small Vessel Disease: An in vivo PET Study With Neuropathological Comparison - Paul Wright; Mattia Veronese; Ndabezinhle Mazibuko; Federico E. Turkheimer; Eugenii A. Rabiner; Eugenii A. Rabiner; Clive G. Ballard; Steven C. R. Williams; Avinash Kumar Hari Narayanan; Avinash Kumar Hari Narayanan; Bahiya Osrah; Bahiya Osrah; et al. (Frontiers in Neurology, 2020)
Small vessel disease (SVD) is associated with cognitive impairment in older age and be implicated in vascular dementia. Post-mortem studies show proliferation of activated microglia in the affected white matter. However, the role of inflammation in SVD pathogenesis is incompletely understood and better biomarkers are needed. We hypothesized that expression of the 18 kDa translocator protein (TSPO), a marker of microglial activation, would be higher in SVD. Positron emission tomography (PET) was performed with the second-generation TSPO ligand [11C]PBR28 in 11 participants with SVD. TSPO binding was evaluated by a two-tissue compartment model, with and without a vascular binding component, in white matter hyperintensities (WMH) and normal-appearing white matter (NAWM). In post-mortem tissue, in a separate cohort of individuals with SVD, immunohistochemistry was performed for TSPO and a pan-microglial marker Iba1. Kinetic modeling showed reduced tracer volume and blood volume fraction in WMH compared with NAWM, but a significant increase in vascular binding. Vascular [11C]PBR28 binding was also increased compared with normal-appearing white matter of healthy participants free of SVD. Immunohistochemistry showed a diffuse increase in microglial staining (with Iba1) in sampled tissue in SVD compared with control samples, but with only a subset of microglia staining positively for TSPO. Intense TSPO staining was observed in the vicinity of damaged small blood vessels, which included perivascular macrophages. The results suggest an altered phenotype of activated microglia, with reduced TSPO expression, in the areas of greatest white matter ischemia in SVD, with implications for the interpretation of TSPO PET studies in older individuals or those with vascular risk factors.